2 | ÷ | x | + | 1 | ÷ | ( | x | + | 12 | ) | = | 1 | ÷ | 90 |
Multiply both sides of the equation by: | x |
2 | + | 1 | ÷ | ( | x | + | 12 | ) | × | x | = | 1 | ÷ | 90 | × | x |
Multiply both sides of the equation by: | ( | x | + | 12 | ) |
2 | ( | x | + | 12 | ) | + | 1 | x | = | 1 | ÷ | 90 | × | x | ( | x | + | 12 | ) |
2 | x | + | 2 | × | 12 | + | 1 | x | = | 1 | ÷ | 90 | × | x | ( | x | + | 12 | ) |
2 | x | + | 2 | × | 12 | + | 1 | x | = | 1 | ÷ | 90 | × | x | x | + | 1 | ÷ | 90 | × | x | × | 12 |
2 | x | + | 24 | + | 1 | x | = | 1 90 | x | x | + | 2 15 | x |
3 | x | + | 24 | = | 1 90 | x | x | + | 2 15 | x |